Diseño de un sistema de costos para la fábrica de tubos “Jesús del Gran Poder”, de la provincia de Cotopaxi, cantón Latacunga, parroquia Eloy Alfaro - Montalvo Maiguashca, Jaime Israel (2022)
The actual integrating project was developed into "Jesús del Gran Poder" pipes factory dedicated to concrete products production and marketing; the entity's problem dwelles in the cost empirical determination and their inadequate control, themselves. The research aim consists to design a cost system, what allows identifying the involved elements into production, profit percentage, furthermore setting sales prices, inventory valuation for decision making. The applied methodology presents a quantitative approach, through a descriptive and field investigation; they were applied techniques, such as: interviews, technical and observation files; got information allowed to identify the costing system, by being designed, considering the entity's needs. The cost system design by processes consists different modules; it has a made systematization, through Excel software, what allows setting a quantity report, an equivalent unit report, a production cost report and a production cost statement. Through the system application can be concluded, which the entity satisfies its information needs by determining the prices and operating profit margin, by virtue, what it is recommended to use a process cost system, which contributes to the profitability levels improvement and business management, through the cost reduction achievement, income increase, profitability maximization and production quality improvements.